Hubungan Konformitas Teman Sebaya dengan Motivasi Belajar di SMA Adabiah Padang - Yuhri Laila; Asmidir Ilyas (Jurnal Neo Konseling, 2019)
Motivation is the need to develop one's abilities optimally, so that they can do better, excel and be creative. Ideally students are more independent in learning, strong learning will. In fact many students are still lazy in learning, have problems in learning such as getting unsatisfactory grades, and there are even students who do not have goals or ideals in themselves. This study aims to (1) describe Peer Conformity, (2) describe learning motivation, (3) test the significance of the relationship of Peer Conformity with learning motivation. This research is a descriptive correlational type of research with quantitative methods. The population of this research is Adabiah Padang High School students. The total sample of 219 students was selected using the Purposive Random Sampling technique. The research instrument used was a peer conformity questionnaire and a learning motivation questionnaire. Data were analyzed with descriptive statistical techniques and Pearson Product Moment techniques with the help of the SPSS For Windows 20.0 program. The research findings show that (1) student peer conformity is in the high category, (2) learning motivation is in the high category, (3) there is a significant positive relationship between peer conformity with learning motivation with a correlation coefficient of -0,502 and a significant level of 0,000